Analysis Of City Branding Strategies In Increasing Visitor Attraction (Case Study On Tourism History Of Marlborough Fort, Bungkarno House In Bengkulu Province) - Reni Indriani; Nora Veronika (UNIVED Press, 2025)
This research aims to analyze the city branding strategy used to increase visitor attraction in Bengkulu Province, with a focus on historical tourism objects such as Fort Marlborough, Bung Karno's House, and the British Cemetery. The research methodology employed was descriptive in nature, utilizing a qualitative approach. Data collection involved conducting interviews with relevant stakeholders and conducting direct observations on-site. Analysis was carried out on the city branding strategy applied to this historical tourism object and its impact on increasing the number of visitors. The research results show that the implementation of city branding in the historical destination of Bengkulu still needs more attention, especially in the aspects of image management, promotion and local community participation.